STUDI LITERATUR KOMPARATIF KARAKTERISTIK RISIKO DAN IMBAL HASIL REKSADANA SAHAM VERSUS UNIT LINK BERBASIS EKUITAS SEBAGAI INSTRUMEN PERENCANAAN KEUANGAN JANGKA PANJANG - Christina Hotmatondini Turnip; Deslia Ningsih Sagala; Krisna Sarinauli Lumbansiantar; Putri Kemala Dewi Lubis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Long-term financial planning demands efficient and goal-appropriate investment instruments. Indonesian retail investors often face confusion between equity mutual funds and equity-based unit-linked insurance plans (ULIPs) due to their similar underlying assets, despite fundamentally different cost structures and risk profiles. This study aims to present a systematic comparative synthesis of the risk-return characteristics of both instruments and to assess their suitability as long-term financial planning vehicles. A Systematic Literature Review (SLR) method was employed, analyzing 15 peer-reviewed articles and relevant OJK regulations. A comparative analysis was conducted across the dimensions of costs, multidimensional risk, returns, and goal suitability. The synthesis reveals that ULIPs impose a multi-layered fee structure including substantial first-year acquisition charges, monthly cost of insurance, and administrative fees that generates a significant expense drag. The effective annual total cost of ULIPs (>5.5%) far exceeds that of equity mutual funds (1.5–3.5%). A simulation assuming an identical 12% annual gross return demonstrates that over 20 years, equity mutual funds can accumulate up to 82% more wealth. ULIPs also carry severe early-year liquidity risk due to surrender charges. Equity mutual funds exhibit superiority in transparency, cost efficiency, and flexibility, making them the superior vehicle for pure long-term wealth accumulation. The 'Buy Term and Invest the Difference' (BTID) strategy is mathematically more optimal. This study recommends strengthened fee transparency for ULIPs and stricter regulatory oversight.